Determinants influencing halal food consumption among generation y Muslims in Malaysian private universities / Aiedah Abdul Khalek - Aiedah, Abdul Khalek (2015)
Previous researches have shown that there are three main determinants of halal consumption, namely attitude, subjective norms and perceived behavioral control. In addition, religiosity has been an important inquiry in human consumption, particularly in halal food consumption. In Malaysia, many initiatives have been conducted by the Malaysian government to encourage halal consumption. However, the influence attitude, subjective norms, perceived behavioral control, religiosity and the government initiatives in influencing halal food consumption among Generation Y as the main food consumers are still vague. Therefore, this study aims to identify and analyze the determinants influencing Generation Y Muslim consumers’ intention in consuming halal food. The Theory of Planned Behavior with two added predictors which are religiosity and the government initiatives is proposed as the conceptual framework. This study employed a quantitative method by using questionnaires to achieve its objectives. Data were collected from 452 respondents from five Private Universities located in the Klang Valley. Descriptive analysis, Exploratory Factor Analysis, Multiple Linear Regression and Moderated Multiple Regression tests were used to analyse the findings. In determining the determinants of behavioral intentions to consume halal food, a five predictors Multiple Linear Regression model was used. In addition, this study, explores the possibility of gender and halal knowledge acquired at the university in moderating the relationship between all five predictors and behavioral intentions in consuming halal food. The results indicated that religiosity, subjective norms and attitude of Generation Y significantly influenced them to consume halal iv food. The findings of this study have also shown that gender plays a moderating role between attitude and behavioral intentions in consuming halal. In a nutshell, this study presents three main contributions which are contribution to the body of knowledge, contribution to the fiqh consumption and to the government in improving policies and strategies of halal food consumption in Malaysia.